ANALISIS DESAIN USER INTERFACE (UI) DAN USER EXPERIENCE (UX) PENGGUNA APLIKASI ANTIMACET - Calvin Wiranata; Arianti; Syamsul Bahri (STMIK KHARISMA Makassar, 2023)
This study was conducted to determine the analysis of user interface design on the user experience of AntiMacet application users by using the Human Centered Design method approach. This analysis data is obtained by distributing statements that have been designed based on the Human Centered Design method approach with the research stages conducting a needs analysis consisting of determining research variables, populations and samples, research hypotheses, research instruments namely the Human Centered Design method, then distributing questionnaires to 30 respondents. , and the data were processed using a Likert scale and conducted a feasibility and validity test. The results of the study obtained a score of 88% on the Inspiration Phase aspect, 87% on the Ideation Phase aspect, 86% on the Implementation phase aspect. So that the average percentage of all aspects assessed is 87%, which proves that the user interface design for the user experience of Anti-Macet application users can be categorized as 'Very Eligible'.